Economic (gross cost) analysis of systematically implementing a programme of advance care planning in three Irish nursing homes. (December 2016) - O'Sullivan, Ronan; Murphy, Aileen; O'Caoimh, Rónán; Cornally, Nicola; Svendrovski, Anton; Daly, Brian; Fizgerald, Carol; Twomey, Cillian; McGlade, Ciara; Molloy, D.
Abstract Background Although advance care planning (ACP) and the use of advanced care directives (ACD) and end-of-life care plans are associated with a reduction in inappropriate hospitalisation, there is little evidence supporting the economic benefits of such programmes. We assessed the economic impact (gross savings) of the Let Me Decide (LMD) ACP programme in Ireland, specifically the impact on hospitalisations, bed days and location of resident deaths, before and after systematic implementation of the LMD-ACP combined with a palliative care education programme. Methods The LMD-ACP was introduced into three long-term care (LTC) facilities in Southern Ireland and outcomes were compared pre and post implementation. In addition, 90 staff were trained in a palliative care educational programme. Economic analysis including probabilistic sensitivity analysis was performed. Results The uptake of an ACD or end-of-life care post-implementation rose from 25 to 76 %. Post implementation, there were statistically significant decreases in hospitalisation rates from baseline (hospitalisation incidents declined from 27.8 to 14.6 %, z = 3.96, p < 0.001; inpatient hospital days reduced from 0.54 to 0.36 %, z = 8.85, p < 0.001). The percentage of hospital deaths also decreased from 22.9 to 8.4 %, z = 3.22, p = 0.001. However, length of stay (LOS) increased marginally (7–9 days). Economic analysis suggested a cost-reduction related to reduced hospitalisations ranging between €10 and €17.8 million/annum and reduction in ambulance transfers, estimated at €0.4 million/annum if these results were extrapolated nationally. When unit costs and LOS estimates were varied in scenario analyses, the expected cost reduction owing to reduced hospitalisations, ranged from €17.7 to €42.4 million nationally. Conclusions Implementation of the LMD-ACP (ACD/end-of-life care plans combined with palliative care education) programme resulted in reduced rates of hospitalisation. Despite an increase in LOS, likely reflecting more complex care needs of admitted residents, gross costs were reduced and scenario analysis projected large annual savings if these results were extrapolated to the wider LTC population in Ireland.